The Effects of Store Atmosphere and Digital Payment on Impulse Buying through Hedonic Shopping Value - Ahmad Ali; Satria Avianda Nurcahyo; Irfan Wildzan Muafa; Muhammad Awal (Economic and Business Horizon, 2026)
The rapid growth of modern retail has intensified competition, encouraging retailers to create shopping experiences that stimulate consumers’ impulse buying behavior. Both store atmosphere and digital payment have become important factors in shaping consumers’ shopping experiences, while hedonic shopping value may explain how these factors influence spontaneous purchasing decisions. This study aims to examine the direct and indirect effects of store atmosphere and digital payment on impulse buying through hedonic shopping. A quantitative approach was employed using a purposive sampling technique involving 150 consumers who had used digital payment methods. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results reveal that store atmosphere and digital payment significantly enhance hedonic shopping value and directly increase impulse buying. Hedonic shopping value also has a significant positive effect on impulse buying and mediates the relationships between store atmosphere, digital payment, and impulse buying. These findings highlight the importance of integrating physical store environments with digital transaction facilities to create enjoyable shopping experiences that encourage spontaneous purchases. The study contributes to consumer behavior literature by demonstrating the complementary roles of experiential and technological factors in explaining impulse buying within the context of Indonesian modern retail.